Proceedings of the 2nd Workshop on Workshop on Physical Analytics 2015
DOI: 10.1145/2753497.2753508
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Shopper's Behavior through WiFi Signals

Abstract: Substantial progress in WiFi-based indoor localization has proven that pervasiveness of WiFi can be exploited beyond its traditional use of internet access to enable a variety of sensing applications. Understanding shopper's behavior through physical analytics can provide crucial insights to the business owner in terms of e↵ectiveness of promotions, arrangement of products and e ciency of services. However, analyzing shopper's behavior and browsing patterns is challenging. Since video surveillance can not used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 11 publications
0
43
0
1
Order By: Relevance
“…CSIs in different locations have been explored by many studies to locate people in a room and have had positive results [10,14,18]. However, we want the features in our method to be insensitive to the locations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CSIs in different locations have been explored by many studies to locate people in a room and have had positive results [10,14,18]. However, we want the features in our method to be insensitive to the locations.…”
Section: Methodsmentioning
confidence: 99%
“…Studies [10,11] have proved that the existence and movement of humans will affect the channel state information (CSI) of wireless signals, and CSI has an advantage over light, infrared, or thermal energy when attempting to infer people’s movements. CSI holds potential for the convergence of accurate and pervasive indoor localization and has attracted numerous recent research efforts [10,11,12,13,14]. Studies [10,11,12] have shown that different actions have different CSI change patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CARM [50] body movements 0.15∼300 WiSee [23] hand gestures 8∼134 WiFinger [27] hand gestures 0.2∼5 WiFinger [26] ASL gestures 1∼60 WiWho [47] gaits 0.3∼2 WiFi-ID [51] walking behavior 20 ∼80 UniBreathe [52] respiration 0.1∼0.5 WiHear [53] mouth 2∼5 Zeng [54] shopping behavior 0.3∼2…”
Section: System Activities Frequency Range (Hz)mentioning
confidence: 99%
“…set(j));19 for x = set(j) : length(nor2) do20 if nor2(x) <= e then21 end-point=x; max(w) − min(w) < threshold then29 (a) Original CSI waveform of 17 consecutive typing gestures; (b) nor1: variance of original waveform ; (c) nor2: data smoothing on nor1; (d) Comparison of nor1 and nor2; (e) Start-point determination for 3rd gesture in original waveform. Since the result tends to be stable after the 7th segment, set the 7th segment point as start-point.…”
mentioning
confidence: 99%